1998
DOI: 10.1542/peds.102.6.e62
|View full text |Cite
|
Sign up to set email alerts
|

A New Pattern of Cerebellar Hemorrhages in Preterm Infants

Abstract: ABSTRACT.Objective. Posterior fossa hemorrhages may be underdiagnosed in surviving neonates, with cerebellar hemorrhage discovered in 10% to 25% of autopsy specimens from very low birth weight infants. Posterior fossa lesions have been difficult to visualize by the traditional ultrasonography approach through the anterior fontanelle. Late in 1994, routine posterior fossa imaging through the posterolateral fontanelle was instituted to improve the ultrasonographic visualization of the posterior fossa in neonates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 23 publications
1
69
0
Order By: Relevance
“…Prenatal cerebellar hemorrhages originate mostly in the subpial external granular layer, a germinal matrix that is thickest at 24 WOG and begins to involute at 30 WOG [20]. Accordingly, the majority of reported prenatal cerebellar hemorrhages have been reported to occur between 18 and 24 WOG.…”
Section: Unilateral Cerebellar Hypoplasiamentioning
confidence: 99%
“…Prenatal cerebellar hemorrhages originate mostly in the subpial external granular layer, a germinal matrix that is thickest at 24 WOG and begins to involute at 30 WOG [20]. Accordingly, the majority of reported prenatal cerebellar hemorrhages have been reported to occur between 18 and 24 WOG.…”
Section: Unilateral Cerebellar Hypoplasiamentioning
confidence: 99%
“…Therefore, cerebellar haemorrhage may have occurred before then. Merrill et al 25 reported that cerebellar haemorrhage may occur within the germinal matrices located in the subpial external granule cell layer, which is thickest at 24 weeks' gestation and begins to involute at 30 weeks' gestation. It seems plausible that the period between the 20th and 24th week of gestation is the most vulnerable for cerebellar haemorrhages.…”
Section: Developmental Findingsmentioning
confidence: 99%
“…Recently, the routine use of cranial sonograms and the use of supplementary sonographic windows focusing on the posterior fossa have resulted in an increased diagnosis of unsuspected CH among clinically stable preterm infants. 17 In our study, very immature infants who died before getting a cranial sonographic exam were not included. It is possible that excluding this group of patients at high risk for CH, although few in number, could have led us to underestimate the risk of mortality with CH.…”
Section: Discussionmentioning
confidence: 99%